Nonholonomic motion planning with special restrictions on the end and via points of the control function - Ratajczak, Joanna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper introduces a new modification to the motion planning algorithm of nonholonomic robotic systems using the endogenous configuration space approach which allows imposing restrictions on control functions. The end and via points define the values which the control function should take in a predefined time, either at the beginning, the end or during the motion time horizon. Such a modification can be used to set the values of the control function, which usually are of velocity-like type, to be physically realizable. The constraints are introduced to the algorithm through the extension of the Jacobian. The efficiency of the presented method is shown with the computer simulation results for a nonholonomic space manipulator. A modified Jacobian motion planning algorithm is used for planning consisting of a sequence of two subtasks.